2020
DOI: 10.2147/dddt.s235207
|View full text |Cite
|
Sign up to set email alerts
|

<p>Paeoniflorin Ameliorates Chronic Hypoxia/SU5416-Induced Pulmonary Arterial Hypertension by Inhibiting Endothelial-to-Mesenchymal Transition</p>

Abstract: Background: Endothelial cells dysfunction is one of the hallmark pathogenic features of pulmonary arterial hypertension (PAH). Paeoniflorin (PF) is a monoterpene glycoside with endothelial protection, vasodilation, antifibrotic, anti-inflammatory and antioxidative properties. However, the effects of PF on PAH remain unknown. Methods: Here, we investigated the efficacy of PF in the SU5416/hypoxia (SuHx) rat model of PAH. Human pulmonary arterial endothelial cells (HPAECs) were exposed to 1% O 2 with or without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…In many cases, molecular mechanisms and intermediate players connecting the two processes have not been detailed, and their elucidation would be beneficial for the field at large. Nonetheless, with that need in mind, by presenting compelling data arguing for utilization of BMP signaling restoration strategies targeting EndMT in the treatment of PH (148,202), and offering a number of mechanistic insights into the BMPR-mediated control over EndMT progression (74,102,163,202), the works discussed above do make a persuasive argument for the development of therapeutics aimed at the reversal of PAH-associated EndMT and pave a way for future explorations (198). Finally, the embryonic origin and developmental importance of both BMP signaling [reviewed in Wang et al (186)], EndMT (115,177), and their connections (109,118) suggest an early deep-rooted interconnection between the two processes that may be subject to temporal regulation and perhaps also suggest a critical coregulation in cell fate determination.…”
Section: The Role Of Hypoxia In Ph-associated Endmtmentioning
confidence: 99%
“…In many cases, molecular mechanisms and intermediate players connecting the two processes have not been detailed, and their elucidation would be beneficial for the field at large. Nonetheless, with that need in mind, by presenting compelling data arguing for utilization of BMP signaling restoration strategies targeting EndMT in the treatment of PH (148,202), and offering a number of mechanistic insights into the BMPR-mediated control over EndMT progression (74,102,163,202), the works discussed above do make a persuasive argument for the development of therapeutics aimed at the reversal of PAH-associated EndMT and pave a way for future explorations (198). Finally, the embryonic origin and developmental importance of both BMP signaling [reviewed in Wang et al (186)], EndMT (115,177), and their connections (109,118) suggest an early deep-rooted interconnection between the two processes that may be subject to temporal regulation and perhaps also suggest a critical coregulation in cell fate determination.…”
Section: The Role Of Hypoxia In Ph-associated Endmtmentioning
confidence: 99%
“…Determining how to improve cellular plasticity and muscularization in PASMCs to reverse pulmonary vascular remodelling may represent a new potential perspective for the treatment of PAH in future studies. Additionally, multiple studies have also demonstrated that the endothelial–mesenchymal transition (EndMT) caused by hypoxia was also a vital factor for pulmonary vascular remodelling in rats [ 23 , 24 ]. At present, due to cardiopulmonary pathophysiology also contributing to neuroinflammation, altered gastrointestinal function, and increased bone marrow-derived cells, PAH could be considered a brain–gut–lung systemic disease [ 25 ].…”
Section: Pathophysiology Of Pahmentioning
confidence: 99%
“…Recently, it has been demonstrated that the monoterpene glycoside paeoniflorin, a molecule with endothelial protection and antifibrotic properties, significantly prevented chronic hypoxia/SU5416-induced PAH in rats, with a therapeutic effect likely being related to its capability to inhibit EndoMT in lung arterial ECs [ 209 ].…”
Section: Main Molecular Pathways Driving Myofibroblast Differentiation From Vascular Wall Residing Cells In Systemic Sclerosis and Relatementioning
confidence: 99%